Interkoneksi Sains dalam Pembentukan Karakter Ilmiah Peserta Didik di Madrasah - fiteriani, ida; Baharudin, Baharudin (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Idea about integration and interconnection of science and the Qur'an is not a new phenomenon in the treasury of Islamic sciences epistemology, because the grand theme of the Qur'an has a transformative and responsive function in answering the dynamics of today's nature problem which requires solving by a saintific-religious approach. In a more specific context to teach science to elementary school students (MI), many urgency benefits for the formation of religious and scientific character of children. Learning science that is designed by integrating and interconnecting science and the Qur'an can be a vehicle laying the groundwork to provide an indept understanding of the connection of the existence of this universe with the Being Substance of the Creator of the universe. When this provision is deeply rooted and forms a belief, and continues until the adult child, the character always